Тип творческой личности в трактовке А.П.Чехова (к 150-летию со дня рождения писателя) - Кожевникова, А.А. (Сумський історико-архівний журнал, 2010)
The issue of sense and importance of creative work, its impact on the personality of the creator in the works of A.P.Chekhov is examined in the publication.